2016
DOI: 10.1111/mbe.12125
|View full text |Cite
|
Sign up to set email alerts
|

Reading‐Specific Flexibility Moderates the Relation Between Reading Strategy Use and Reading Comprehension During the Elementary Years

Abstract: The goal was to test whether cognitive flexibility moderates the relation between reading strategy use and reading comprehension during the elementary years. Seventy‐five second‐ through fifth‐grade students completed a think aloud task and a metacognitive questionnaire to measure reading strategies, two card‐sorting tasks to measure general and reading‐specific cognitive flexibility, and one standardized measure of reading comprehension, as well as measures of oral reading fluency and vocabulary. As expected,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…Interestingly, the final model included paths from working memory and inhibitory control to delay of gratification, suggesting intriguing relations among cool and hot aspects of executive functioning. Previous findings have shown that complex executive functions depend on simpler aspects, which is consistent with our findings (Dawson & Guare, ; Gnaedinger et al, ; Meltzer, , ). Age did not predict delay of gratification directly, as it did the cool executive functions.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Interestingly, the final model included paths from working memory and inhibitory control to delay of gratification, suggesting intriguing relations among cool and hot aspects of executive functioning. Previous findings have shown that complex executive functions depend on simpler aspects, which is consistent with our findings (Dawson & Guare, ; Gnaedinger et al, ; Meltzer, , ). Age did not predict delay of gratification directly, as it did the cool executive functions.…”
Section: Resultssupporting
confidence: 94%
“…Our original model did not include paths between executive function components; however, it is quite plausible that the components are related in meaningful ways. For instance, basic executive function processes may set the stage for more complex executive functions (Dawson & Guare, ; Gnaedinger, Hund, & Hesson‐McInnis, ; Meltzer, , ). With this conceptualization in mind, we allowed working memory to predict delay of gratification, which improved the model fit.…”
Section: Resultsmentioning
confidence: 99%
“…A study independent of the DIME model, also employing structural equation modeling, found that comprehension strategies (and working memory) predicted reading ability in a model that included reading fluency and vocabulary (Muijselaar et al, 2017). Although these models did not include an array of EF skills, it is notable that some research has suggested that GSF may mediate the relation between strategy use and reading ability (Gnaedinger, Hund, & Hesson‐McInnis, 2016).…”
Section: Active Self‐regulation Is Central To Readingmentioning
confidence: 99%
“…It is a consensus among scholars that executive functions are important for reading comprehension (Abreu et al, 2014;Bovo et al, 2016;Gnaedinger, Hund, & Hesson-McInnis, 2016;Fadaei et al, 2017;Locascio et al, 2010;Sesma et al, 2009). Thus, once the recognition and decoding of frequent words is automated, the executive functions act so that this process occurs smoothly, collaborating with the understanding of what is being read, that is, of comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, once the recognition and decoding of frequent words is automated, the executive functions act so that this process occurs smoothly, collaborating with the understanding of what is being read, that is, of comprehension. Although some scholars point out that EF are more predictive of reading comprehension than decoding (Sesma et al, 2009), due to the role that high EF (such as planning and monitoring) have in reading comprehension (Locascio et al, 2010;Sesma et al ., 2009), the basic EF, such as: working memory (Abreu et al, 2014;Bovo et al, 2016;Sesma et al, 2009), cognitive flexibility (Abreu et al, 2014;Gnaedinger et al, 2016), inhibitory control (Arrington et al, 2014;Bovo et al, 2016), and verbal fluency (Bovo et al, 2016;Smith-Spark et al, 2017), are also shown to be related to a deficit in reading comprehension.…”
Section: Discussionmentioning
confidence: 99%